The Right to Freedom of Express Opinions in Public Based on Pancasila - Triwahyuningsih Triwahyuningsih (Law Doctoral Program Universitas Muhammadiyah Surakarta, 2021)
Freedom to express opinions in public is a human right guaranteed by the 1945 Indonesian Constitution and the Universal Declaration of Human Rights. The concept of human rights originating from the West resulted in its application often causing problems. This problem arises because the values of freedom that are generally upheld in the West are different from the specific values based on the philosophy and way of life in each country. The purpose of this study is to describe how the freedom to express opinions in public is in accordance with the values of Pancasila ideology. This research is normative legal research with a statute approach and a conceptual approach. Using primary and secondary legal materials also analyzed qualitatively descriptively. The results of the study conclude that the right to express freedom in public must be in accordance with the values of Pancasila, which is to fulfill the principle of balance between the rights and obligations of every citizen with the goal of responsible freedom being realized. Rights should not be understood only as claims on others, but also contain an obligation to respect the rights of others. Rights always have implications for obligations. All obligations, like all rights, derive from law, because all obligations are moral imperatives and all moral imperatives arise from law. Its application always upholds the values of divinity, humanity, unity, democracy and aims to realize social justice for all Indonesian people.Keywords: right of freedom, express opinion, Pancasila